Pengaruh E-Wom, Brand Image dan Service Quality Terhadap Keputusan Berlangganan Platform Streaming di Disney+ Hotstar - Muhammad Yoga Adhi Pramana; R. Rahmawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The growth of technology in the current digital era has changed the way people consume TV series entertainment. Disney+ Hotstar as one of the main streaming platforms in this streaming market. In the world of marketing Disney+ Hotstar requires an effective marketing plan to attract consumer attention. The objectives of this study are (1) To determine the influence of E-WOM on the decision to subscribe to the streaming platform on Disney+ Hotstar. (2) To determine the influence of Brand Image on the decision to subscribe to the streaming platform on Disney+ Hotstar. (3) To determine the influence of Service Quality on the decision to subscribe to the Disney+ Hotstar streaming platform (4) To determine the influence of E-WOM, Brand Image and Service Quality on the decision to subscribe to Disney+ Hotstar. The method used is quantitative with multiple linear regression analysis. The sample in this study amounted to 108 respondents. The results of the study show that (1) E-WOM has a positive but not significant effect on the Subscription Decision. (2) Brand Image has a positive and significant effect on Subscription Decisions. (3) Service Quality has a positive and significant effect on Subscription Decisions. (4) Simultaneously, E-WOM, Brand Image, and Service Quality have a significant effect on Subscription Decisions.